Adventitious Shoot Regeneration from Leaf Explant of Dwarf Hygro (Hygrophila polysperma (Roxb.) T. Anderson). (17th June 2013) - Karataş, Mehmet; Aasim, Muhammad; Çınar, Ayşegül; Dogan, Muhammet
Abstract : Dwarf hygro ( Hygrophila polysperma ) is an ornamental aquatic plant that changes its leaf colours to pinkish in high light. It is listed as a medicinal plant in medicinal plant lists of Indian states of West Bengal and Karnataka. It is also used as a screening tool for toxicities and a bioindicator to detect and control algae. The study reported in vitro adventitious shoot regeneration from leaf explants cultured on MS medium containing 0.10–1.60 mg/L Kin/TDZ with or without 0.10 mg/L IBA and 500 mg/L Amoklavin to eradicate endogenic bacterial contamination. Direct adventitious shoot regeneration started within one week from both culture mediums followed by late callus induction which was more prominent on TDZ containing media compared to Kin containing media. Addition of 0.10 mg/L IBA with both Kin and TDZ increased shoot regeneration frequency, mean number of shoots per explant, and mean shoot length. Maximum number of 16.33 and 20.55 shoots per explant was obtained on MS medium containing 0.80 + 0.10  mg/L Kin-IBA and 0.10 + 0.10  mg/L TDZ-IBA, respectively. Regenerated shoots were rooted on MS medium containing 0.20–1.00 mg/L IBA followed by successfull acclimatization in aquariums. Regenerated plantlets were also tested in jars containing distilled water that showed the pH 6–9 for the best plant growth and development.